Remarks by Professor Arnoud De Meyer, SMU President At the Launch of SMU GROW, 6 January 2015 - Singapore Management University (Institutional Knowledge at Singapore Management University, 2015)
Embarking on GROW advocates the start of a new dimension of growth for SMU, especially as we start SMU’s 15th year. We believe that in a transformative education, social good and all-rounded learning is at the heart of academic pursuit; and ‘U’ includes not just the University campus and students, but many individuals and organisations that matter and transform ‘U’. Knowledge and growth have no boundaries and everyone is a student in society. Growing a garden physically and in your heart brings the community back to fundamental basics that are important to life. We need to produce food for our body and soul, and are responsible for a better and greener future, through our own hands. A real education must make the lives of others better. And we want to start with the community right where we are, within the Central CDC.